2022
DOI: 10.1063/5.0091976
|View full text |Cite
|
Sign up to set email alerts
|

Efficient routing for spatial networks

Abstract: In many complex networks, the main task is to transfer load from sources to destinations. Therefore, the network throughput is a very important indicator to measure the network performance. In order to improve the network throughput, researchers have proposed many effective routing strategies. Spatial networks, as a class of complex networks, exist widely in the real-world. However, the existing routing strategies in complex networks cannot achieve good results when applied in spatial networks. Therefore, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…However, in the spatial network, this relationship is not that obvious. Lin et al [33] investigated the influence of network topology on load transmission. They found that the nodes with larger links and closer to the regional center usually process more loads.…”
Section: Degree-location Routing Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…However, in the spatial network, this relationship is not that obvious. Lin et al [33] investigated the influence of network topology on load transmission. They found that the nodes with larger links and closer to the regional center usually process more loads.…”
Section: Degree-location Routing Strategymentioning
confidence: 99%
“…For example, in the topological networks, the node degrees often exhibit an obvious power-law relationship with the loads when adopting the SP routing strategy. However, Lin et al [33] found that this power-law relationship is not obvious in spatial networks. Most of the existing routing strategies cannot achieve great results in spatial networks.…”
mentioning
confidence: 99%